The Standing To Blame, or Why Moral Disapproval Is What It Is. (21st July 2019) - Riedener, Stefan
Abstract : Intuitively, we lack the standing to blame others in light of moral norms that we ourselves don't take seriously: if Adam is unrepentantly aggressive, say, he lacks the standing to blame Celia for her aggressiveness. But why does blame have this feature? Existing proposals try to explain this by reference to specific principles of normative ethics – e.g. to rule‐consequentialist considerations, to the wrongness of hypocritical blame, or principles of rights‐forfeiture based on this wrongness. In this paper, I suggest a fundamentally different approach. Employing Timothy Williamson's idea of 'constitutive rules' of speech acts, I argue that this feature of blame is simply constitutive of any essentially moral form of disapproval. So if Adam had the standing to disapprove of Celia's aggressiveness in some form, necessarily, this disapproval couldn't be blame. If I'm right, this proposal thus not only answers our main question, but also sheds an interesting novel light on the very nature of blame. If we didn't have a form of disapproval with that feature, we wouldn't have our practice of holding each other to moral norms.